An Analysis Of The Impact Of Credit Cards In International Finance Focusing On The United States Of America - Dr. Alok Kumar, Dr. Ajay Kumar Gupta (European Economic Letters (EEL), 2025)
According to the Federal Reserve, the amount of credit card debt in the United States reached a record high of USD 1.14 trillion in Q2 2024. How does financial literacy affect credit card debt repayment in this day and age of sophisticated, high-interest credit cards? Furthermore, how can education and financial literacy help to reduce the rise of credit card debt in the United States? To answer these questions, we use microdata from the most current wave of the 2022 Consumer Finance Survey. Our purpose is to track the likelihood of credit card repayment trends based on the monthly amounts owed by 3865 credit card customers. We explore three forms of self-reported credit card repayment behaviour: rarely, occasionally, and nearly often. Because our outcome variable is ordinal, we use a variety of likelihood-ratio and Brant tests to assess the assumption of proportional probabilities across answer categories. After the tests fail, we use a generalised ordered logit/partial proportional odds model, which allows us to relax the parallel lines restriction for variables that do not require it. We explore a wide range of demographic parameters in our logistic regressions, and we highlight the following findings: The odds of switching to a higher category of payback behaviour for credit card holders with low financial literacy are 21%, which is much lower than the odds for respondents with high financial literacy. Furthermore, in comparison to credit card holders without a college degree, those with a college degree are 2.49 times more likely to pay off their obligations on a regular or almost regular basis as opposed to sometimes or scarcely ever. Members of minority groups, women, those under 45, those with dependents, and those earning less than 50,000 USD are more likely to have poor credit card payment habits. In our conclusion, we discuss measures to improve credit card repayment rates. We emphasise the need of keeping an eye on individuals. We also wish to provide some groups with better financial advise.